MITIGATION DOMESTIC VIOLENCE: A COMPERATIVE STUDY OF GOVERNMENT: Interventions in Central Aceh and Banda Aceh - Yuhermansyah, Edi; Rispalman, Rispalman; Balkis Suci, Nada (Universitas Islam Negeri Ar-Raniry, 2026)
Cases of domestic violence (DV) against women and children continue to increase significantly in various regions of Indonesia, including Aceh, necessitating more effective mitigation efforts from government agencies, particularly the DP3A. This research is based on three main questions: the factors contributing to the increase in DV, the forms of mitigation efforts undertaken by the DP3A, and the effectiveness of the DP3A's role in preventing violence. Using a qualitative research method with a juridical-empirical approach, this study combines field observation and data analysis of cases that have not been formally documented. Initial findings indicate a drastic increase in domestic violence cases in Central Aceh Regency, from 33 cases in 2020 to 84 cases in 2024. Meanwhile, Banda Aceh City recorded 683 cases of violence against women and children between 2020 and 2024, making it the highest area in Aceh. The research findings indicate that the increase in violence cases is influenced by economic factors, unequal power dynamics, and a weak social support system. DP3A mitigation efforts include prevention, handling, and recovery, but their effectiveness is still hampered by limited resources and poor inter-agency coordination. This research underscores the importance of strengthening more systematic, integrated, and community-based mitigation strategies to reduce violence against women and children.